2013
DOI: 10.4028/www.scientific.net/amm.368-370.741
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aluminum Hydroxide and Expandable Graphite on the Flammability of Polyisocyanurate-Polyurethane Foams

Abstract: The aim of this work was to verify the influence of expandable graphite (EG) and aluminum hydroxide (ATH) fillers on the flammability of polyisocyanurate-polyurethane (PIR). Limited oxygen index increased to 72.5 with an incorporation of 16 phr (parts per hundred of matrix) EG and 50 phr ATH into the matrix (total weight percent was 39.76%). Cone calorimetry was employed to study the flammability properties of these PIR/ATH/EG composites. Scanning electron microscopy analysis was conducted to study the char ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Figure (a,b) shows HRR and THR behavior for 1.5% phosphorus containing foam made with PPA–PO polyol. Addition of compounds like expandable graphene and aluminum hydroxide showed a reduction in the time of ignition . However, reactive FR based on phosphorus showed an increase in time required for ignition .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure (a,b) shows HRR and THR behavior for 1.5% phosphorus containing foam made with PPA–PO polyol. Addition of compounds like expandable graphene and aluminum hydroxide showed a reduction in the time of ignition . However, reactive FR based on phosphorus showed an increase in time required for ignition .…”
Section: Resultsmentioning
confidence: 98%
“…They can be either powder, liquid, non‐reactive, reactive, radical scavenger, non‐calorific additives and thermally stable compounds incorporated during the foaming process . Additive FRs including dimethyl methyl phosphonate (DMMP), expandable graphene, melamine, metal hydroxides, and nano‐additives are widely reported to be used for introducing flame retardancy within the foams . However, in‐compatibility due to non‐reactive nature of additives tends to reduce the mechanical performance of the rigid foams when added in increased concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Flame retardant polyurethanes foams have been prepared by addition of various flame retardant compounds such as compounds containing phosphorus and/or nitrogen groups, expendable graphite, MgO, and Al 2 O 3 . It was observed that expandable graphite and nitrogen‐based derivatives require higher loading as additive to achieve decent flame retardancy .…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the SEM images of foams containing different wt % P. Foams with 0 and 2 wt % P showed almost identical cellular morphology. AFRs such as DMMP acts as a plasticizer and increases the cellular size, while melamine or expandable graphene tend to open the cellular structure limiting their practical applicability as an FR for rigid foams . However, RFR synthesized in this study shows no adverse effect on the cellular structure of the foams.…”
Section: Resultsmentioning
confidence: 77%